The opportunities to build on existing expertise in writing classrooms: a study of writing lessons in New Zealand primary schools. Issue 6 (1st November 2016) - Jesson, Rebecca N.; Cockle, Victoria
Abstract : The present study investigated 15 Year 4–6 classrooms in two multicultural schools in New Zealand to understand what opportunities students had to draw on their diverse experiences of texts. A mixed-methods approach was taken, including classroom observations and student interviews. Results suggested that lessons were characterised by a consistent format of teacher-led, whole class instruction followed by independent writing. Conversations about prior knowledge typically sought display of taught items. Students saw few links between writing forms in school and texts out of school. The study highlights the role of lesson structure in framing incorporation of prior knowledge in writing lessons.